Pengaruh Pendapatan Asli Daerah Dan Dana Perimbangan Terhadap Belanja Daerah di Kota Banjarmasin - Hapsa, Syiblia Deya; Saipudin (PPJP ULM, 2019)
This research was conducted to analyze the factors that influence Regional Expenditures in Banjarmasin City. With reference to the variable Regional Original Income (PAD), the Balancing Fund. In principle, the greater the contribution of PAD to expenditure will show the smaller regional dependence on the center. where regional expenditure can be influenced by PAD and Balancing Funds. Data used is secondary data consisting of Times Series Data the 2007 period 2016, where the data is analyzed using multiple linear regression models, wich is seen as from the magnitude of R2 seen from the test coefficient of determination, testing variables simultaneously ( Test F ) and partly ( T Test ). To find out whether Regional Original Revenue and influential Balancing Funds on Regional Expenditure in Banjarmasin city. The result of this study indicated that the Regional Original income variable has a significant effect on regional Expenditure, while the balancing fund has no significant effect on Regional Expenditure.